Respiratory Syncytial Virus Infection in Children with Bronchiolitis (Journal of Bangladesh College of Physicians and Surgeons, 2024)
Background: Respiratory Syncytial Virus (RSV) is the most common organism causing bronchiolitis. Bronchiolitis is almost always diagnosed clinically. As a result, the availability of bedside sensitive rapid RSV antigen tests is critical for timely RSV acute respiratory infection diagnosis.Methods and materials: This study was conducted to detect RSV antigen positivity and the sociodemographic profile of children with RSV antigen positive bronchiolitis. From October 2022 to March 2023, this observational study was conducted in the pediatrics department of Chattogram Medical College Hospital. Ninety-two nasopharyngeal swabs from children younger than two years, were tested for RSV antigen. The mean and standard deviation were used to express the demographic data. Chi-square analysis was used to examine differences in group proportions.Results: RSV antigen positivity was detected in 45.7% of the 92 cases, with a mean age of 4.18±3.08 months. Severe bronchiolitis cases were more common (22.8%) among antigen positive cases and had the longest hospital stay. During the months of November (42.4%) and December (29.3%), RSV infection levels peaked. This study describes that during the seasonal epidemics, RSV was the main concern, as the number of positive cases decreased in the months that followed. The signs and symptoms of RSV positive and negative cases were not significantly different.Conclusion: A simple, low-cost and bedside RSV test can be considered as a valuable diagnostic tool in a low resource setting.J Bangladesh Coll Phys Surg 2024; 42: 368-378